Self-enforcing path dependent trajectories? A comparison of the implementation of the EU energy packages in Germany and the Netherlands - Simon Fink; Eva Ruffing; Luisa Maschlanka; Hermann Lüken genannt Klaßen (Regulation & Governance, 2024)
Since the 1990s, the EU has attempted to create a common electricity market. However, EU legislators are unsatisfied by the results. We argue that differentiated implementation of directives over time creates path dependencies that entrench national differences. The actor constellation of parties and incumbent operators at the beginning of the liberalization path determines how well countries implement liberalizing directives. The implementation, in turn, changes the actor constellation for the next directive, increasing or decreasing the institutional power of incumbents. We illustrate our argument analyzing the implementation of the first three energy market packages in Germany and the Netherlands. Both countries had similar electricity markets at the beginning of market liberalization, but their actor constellation was slightly different. German implementation gradually strengthened vertically integrated utilities, while Dutch implementation dismantled these utilities through unbundling. These paths became self-reinforcing, counteracting European harmonization efforts.
Keywords: 330; Energy policy; path dependency; policy implementation